Cardiac magnetic resonance imaging: a new tool to identify cardioaortic sources in ischaemic stroke. Issue 1 (22nd September 2016) - Yaghi, Shadi; Liberman, Ava L; Atalay, Michael; Song, Christopher; Furie, Karen L; Kamel, Hooman; Bernstein, Richard A
Abstract : Stroke of undetermined aetiology or 'cryptogenic' stroke accounts for 30–40% of ischaemic strokes despite extensive diagnostic evaluation. The role and yield of cardiac imaging is controversial. Cardiac MRI (CMR) has been used for cardiac disorders, but its use in cryptogenic stroke is not well established. We reviewed the literature (randomised trials, exploratory comparative studies and case series) on the use of CMR in the diagnostic evaluation of patients with ischaemic stroke. The literature on the use of CMR in the diagnostic evaluation of ischaemic stroke is sparse. However, studies have demonstrated a potential role for CMR in the diagnostic evaluation of patients with cryptogenic stroke to identify potential aetiologies such as cardiac thrombi, cardiac tumours, aortic arch disease and other rare cardiac anomalies. CMR can also provide data on certain functional and structural parameters of the left atrium and the left atrial appendage which have been shown to be associated with ischaemic stroke risk. CMR is a non-invasive modality that can help identify potential mechanisms in cryptogenic stroke and patients who may be targeted for enrolment into clinical trials comparing anticoagulation to antiplatelet therapy in secondary stroke prevention. Prospective studies are needed to compare the value of CMR as compared to transthoracic and transesophageal echocardiography in the diagnostic evaluation of cryptogenic stroke.